Usage of computer unit and associated factors among medical students of the University of Jaffna - Dinusha, W.A.W.; Rathnayaka, R.S.T.; Sahra, M.N.F.; Nirupama, L.G.U.; Shanu, M.P.; Kumarendran, B.; Murugananthan, A. (University of Jaffna, 2024)
Background and objective: A computer unit was established in 2021 at the Faculty of Medicine, University of Jaffna, to support computer-based learning. Despite its availability, it is not used sufficiently by the students. The objective of this study was to describe the usage of the computer unit and associated factors among medical students at the University of Jaffna. Methods: The study employed a mixed-methods approach, combining quantitative (cross-sectional analysis) and qualitative (focus group discussions) components. The cross-sectional study involved 426 participants selected through stratified random sampling from medical students at the Faculty of Medicine, University of Jaffna. Data were collected using a self-administered questionnaires and analysed with SPSS 20 software. The focus group discussions were coded and analysed thematically. Results: The study reported a high response rate of 97.7%. The sample consisted of mainly females (61.8%); 85.6% reported owning smartphones with 69.2% of participants having sufficient monthly income. Awareness of the computer unit was positive (83.4%), but only 1.7% knew its operating hours. Surprisingly, 74% of respondents did not use the unit. Out of the 26% respondents who did, 57.4% used it for research, and 38% for online learning. The primary reason for not using the unit was having personal devices (74.7%). Notably, 42.1% were aware of unlimited data, while 11.8% knew about secure data storage. Suggestions included, adding photocopy and printing facilities (64.7%) to improve utilization. During the focus groups, participants discussed computer unit usage, emphasizing research and document preparation. According to the thematic analysis, challenges with use included limited awareness and slow machines; interference with lectures; and preferring personal devices. Expectations for the future included increased usage with improved access and extended operating hours. Conclusion and recommendations: Awareness of specialized facilities significantly impacted computer unit utilization, emphasizing the need for promoting such awareness among students. Family income and internet usage did not correlate with computer unit usage. Qualitative findings underscored a lack of awareness among students, who often preferred personal mobile devices over computers. These results highlight the importance of targeted strategies to enhance awareness and tailor interventions to improve computer unit utilization among medical education.
Keywords: Information and communication technology; Computer unit; Medical education